2019
DOI: 10.1016/j.dental.2019.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different pretreatments and aging procedures on the flexural strength and phase structure of zirconia ceramics

Abstract: OBJECTIVE To test the impact of zirconia pretreatment and aging on flexural strength and phase structure. METHODS For flexural strength measurements, 180 3Y-TZP 0.25 specimens were fabricated and pretreated: (i) air-abraded (105-m alumina, 0.25MPa), (ii) air-abraded (50-m alumina, 0.25MPa), (iii) air-abraded (30-m silica-coated alumina, 0.28MPa) (iv) non-pretreated. Each pretreated group (n=15) was aged: (a) hydrothermal (134°C, 0.23MPa, 2h) (b) in a mastication simulator (1,200,000×, 5/55°C) and (c) not aged.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
(96 reference statements)
2
14
0
12
Order By: Relevance
“…Cotic et al 42 determined a more than two‐fold slower aging rate at initial stages of aging in air‐abraded specimens compared with as‐sintered ones. Similar results were also revealed by other studies that emphasized the possible protective effect of the compressive layer 17,41 . Consequently, it is possible to say that the immediate zirconia surface is a deciding factor of susceptibility to LTD 42 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Cotic et al 42 determined a more than two‐fold slower aging rate at initial stages of aging in air‐abraded specimens compared with as‐sintered ones. Similar results were also revealed by other studies that emphasized the possible protective effect of the compressive layer 17,41 . Consequently, it is possible to say that the immediate zirconia surface is a deciding factor of susceptibility to LTD 42 …”
Section: Discussionsupporting
confidence: 87%
“…15,16 However, in dental literature, the effect of air-abrasion on the mechanical strength of zirconia is still controversial. After this treatment, some reports stated an increase in flexural strength, probably because of the residual compressive stress at the surface as a result of phase transformation, [17][18][19][20][21] yet others concluded an unfavorable effect because of substantial surface damage. [22][23][24] Unlike the earlier studies that concentrated on evaluating the effects of pretreatments after zirconia sintering, recent studies have focused on airborne-particle abrasion before sintering.…”
mentioning
confidence: 99%
“…The present results also come in agreement with De souza et al, [41] and Kelch et al, [42] , who analyzed the influence of hydrothermal aging on zirconia and stated that hydrothermal aging affects monoclinic phase content and surface topography.…”
Section: Translucency Evaluation Was Evaluated By Calculating Contrassupporting
confidence: 93%
“…Similar to the CAD/CAM polymers DFC and PICN evaluated in this study, zirconia requires surface treatment to obtain reliable adhesion [ 30 , 31 , 32 , 33 ]. In the zirconia material, several changes in material properties occur on varying the pressure intensity; two contradictory results have been reported on the effect of air abrasion pressure on zirconia material.…”
Section: Discussionmentioning
confidence: 99%
“…In the zirconia material, several changes in material properties occur on varying the pressure intensity; two contradictory results have been reported on the effect of air abrasion pressure on zirconia material. Some studies reported that surface treatment using air abrasion caused tetragonal–monoclinic transformation toughening and formation of a compressive layer on the surface of the zirconia material that improved its flexural strength [ 30 , 31 , 32 ]. Other studies have reported that the flexural strength decreased as flaws (e.g., cracks) formed on the surface [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%